Alternating Red and Blue Light-Emitting Diodes Allows for Injury-Free Tomato Production With Continuous Lighting - Lanoue, Jason; Zheng, Jingming; Little, Celeste; Thibodeau, Alyssa; Grodzinski, Bernard; Hao, Xiuming (Frontiers in Plant Science, 2019)
Plant biomass is largely dictated by the total amount of light intercepted by the plant (daily light integral (DLI) – intensity × photoperiod). Continuous light (CL, 24h lighting) has been hypothesized to increase plant biomass and yield if CL does not cause any injury. However, lighting longer than 18h causes leaf injury in tomato characterized by interveinal chlorosis and yield is no longer increased with further photoperiod extension in tomatoes. Our previous research indicated the response of cucumbers to long photoperiod of lighting varies with light spectrum. Therefore, we set out to examine greenhouse tomato production under supplemental CL using an alternating red (200µmol m-2 s-1, 06:00-18:00) and blue (50µmol m-2 s-1, 18:00-06:00) spectrum in comparison to a 12h supplemental lighting treatment with a red/blue mixture (200µmol m-2 s-1 red + 50µmol m-2 s-1 blue, 06:00-18:00) at the same DLI. Our results indicate that tomato plants grown under supplemental CL using the red and blue alternating spectrum were injury-free. Furthermore, parameters related to photosynthetic performance (i.e., Pn¬max, quantum yield, and Fv/Fm) were similar between CL and 12h lighting treatments indicating no detrimental effect of growth under CL. Leaves under CL produced higher net carbon exchange rates (NCER) during the subjective night period (18:00-06:00) compared to plants grown under 12h lighting. Notably, 53 days into the treatment, leaves grown under CL produced positive NCER values (photosynthesis) during the subjective night period, a period typically associated with respiration. At 53 days into the growth cycle, it is estimated that leaves under CL will accumulate approximately 800 mg C m-2 more than leaves under 12h lighting over a 24h period. Leaves grown under CL also displayed similar diurnal patterns in carbohydrates (glucose, fructose, sucrose, and starch) as leaves under 12h lighting indicating no adverse effects on carbohydrate metabolism under CL. Taken together, this study provides evidence that red and blue spectral alternations during CL allow for injury-free tomato production. We suggest that an alternating spectrum during CL may alleviate the injury typically associated with CL production in tomato.